Peningkatan Pembinaan Sadar Wisata Dalam Pengembangan Pariwisata Pada Sentral IKM Batik Malon - Nina Mistriani; C.Susmono Widagdo; Ray Octafian (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
Tourism is a mainstay for the development of new leading tourist attractions or destinations. Pokdarwis (Tourism Awareness Group) is a key element for the community with its strategic role in developing and managing the natural, cultural, and artificial potential of a region to become a tourist destination. This community service activity aims to strengthen the institutional function of the Batik Small and Medium Industries (IKM) in understanding the potential elements of Sapta Pesona (Seven Charms). The implementation of Sapta Pesona is an effort to provide excellent service to tourists, especially for tourism villages, so the participation of the Batik IKM central community is needed in managing the 7 elements of Sapta Pesona. The Sapta Pesona campaign aims to recognize and gain experience in developing tourism villages that have become tourist attractions, through stages of recognizing and gaining experience in managing community-based tourism products and implementing Sapta Pesona actions in the management of tourism villages.